Responsabilidade social sob a ótica do assédio moral: o caso furnas - Souza Junior, Hélio Araújo de (2003)
The objectives of this research were to identify and to determine the mam elements presents in actions developed by the company classified as corporate social responsibility as well as the company's speech and relation with their employees1 in Fumas' productive units. In the base theoretician-empiricist, were analyzed the aspects concerning to the social management considering the postindustrial societal model, as to the social responsibility and the moral siege aspect present in the internaI company' s relations. The method that characterizes this research is the case study of a mixing economy company considered as prominence in the industrial scene of the country, from the verification of its organizational climate. The data had been gotten by direct comment and by semistructuralized interviews, carried through with workers belonging to diverse hierarchic organization's studied leveIs, involved with social practices and their organization, having relationship to the employees. The analysis was description-qualitative formo The collected data disclose to the existence of accords and dissonances between the social responsibility practical, the moral siege and the speech presented by this company. The main objective of the study was to extend the agreement concerning to the social responsibility, as well as the moral siege practiced by the company, having as reference their integrant's perceptions, considering both the current economic and social rationalities that establish a new mo dei of relationship between State, companies under its protection and the civil society.